1989
DOI: 10.1136/gut.30.7.1020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to the long acting somatostatin analogue SMS 201-995 in a child with congenital microvillus atrophy.

Abstract: SUMMARY A 27 month old girl with congenital microvillus atrophy received two courses of SMS 201-995, a synthetic long acting analogue of native somatostatin, in an attempt to decrease profuse secretory diarrhoea. During the first trial at 13 months of age fluid and electrolytes administered by parenteral infusion were decreased as measured by water and faecal electrolyte losses. During the second trial of SMS 201-995 at 19 months fluid and electrolyte input were held constant for 14 days. Stool volume declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…All forms of pharmacological intervention to control watery diarrhea have failed including steroids, somatostatin analogues (octreotide), loperamide, or the administration of epidermal growth factor [3,22]. There are case reports where the stool output could be reduced by pharmacotherapy, but enteral nutrition was still not possible [23]. In single patients with mild symptoms, especially patients with a late onset or atypical form, spontaneous remission has been described [24].…”
Section: Therapymentioning
confidence: 99%
“…All forms of pharmacological intervention to control watery diarrhea have failed including steroids, somatostatin analogues (octreotide), loperamide, or the administration of epidermal growth factor [3,22]. There are case reports where the stool output could be reduced by pharmacotherapy, but enteral nutrition was still not possible [23]. In single patients with mild symptoms, especially patients with a late onset or atypical form, spontaneous remission has been described [24].…”
Section: Therapymentioning
confidence: 99%
“…7 It has several gastrointestinal actions. [8][9][10][11] Octreotide induces phase III of the migrating motor complex in the small intestine. 12 Von der Ohe et al conducted a randomized blind study assessing the regional effects of octreotide on the gastrointestinal tract; the study showed improvement in the colonic motility index and statistically significant phasic pressure activity in the octreotide group compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical trials of various medical therapies, including high dose corticosteroid, pentagastrin, human colostrum, epidermal growth factor, clonidine, and somatostatin or its long acting analogue octreotide, have been reported (1)(2)(3)(4). Of these, only somatostatin or its analogue octreotide was effective in decreasing the volume of diarrhea and preventing recurrent episodes of dehydration (24). However, in no instance has medical therapy prevented reliance on parenteral nutrition and intravenous fluid replacement therapy for massive, ongoing intestinal losses.…”
Section: Discussionmentioning
confidence: 99%